2019
DOI: 10.1007/s40475-019-00193-y
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E in Pregnant Women and the Potential Use of HEV Vaccine to Prevent Maternal Infection and Mortality

Abstract: Purpose of Review Hepatitis E (HEV) is a continuing public health problem in developing countries, causing high mortality in pregnant women. This article reviews the latest knowledge on HEV in pregnancy, the vaccine candidates that have reached clinical trials, and their potential use during pregnancy. Recent Findings New evidence suggests that a genotype-specific tropism to uteroplacental cells contributes to the multifactorial pathology leading to the increased severity of HEV during pregnancy. Data from pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…We reported the incidence of HEV infection in pregnant women of 11.8% (Table 7 ). Studies from China demonstrated that the anti-HEV IgM antibody's detection rate in pregnant women ranged from 0.6 to 4.11% [ 18 20 , 29 ]. These studies screened pregnant women during their antenatal and postpartum visits, most of which were not presented with clinical hepatitis, unlike our study.…”
Section: Discussionmentioning
confidence: 99%
“…We reported the incidence of HEV infection in pregnant women of 11.8% (Table 7 ). Studies from China demonstrated that the anti-HEV IgM antibody's detection rate in pregnant women ranged from 0.6 to 4.11% [ 18 20 , 29 ]. These studies screened pregnant women during their antenatal and postpartum visits, most of which were not presented with clinical hepatitis, unlike our study.…”
Section: Discussionmentioning
confidence: 99%
“…The role of HEV-gt1 is increasingly being recognized in causing infection and dysregulation at the maternal–fetal interface which leads to vertical transmission and increased systemic inflammation and consequent severe maternal disease [ 187 ]. Based on HEV transplacental transmission to the fetus, Bose et al [ 188 ] studied placental HEV replication in 90 pregnant women (HEV-AVH 68 and HEV-ALF 22) and detected replicative HEV RNA and HEV RNA staining by ORF3, which correlated with fetal and maternal mortality in HEV-ALF patients.…”
Section: Proposed Hypothesis On Pathogenesis Of Mortality In Hev-infected Pregnant Womenmentioning
confidence: 99%
“…Mothers are predisposed to increased morbidity, primarily due to the development of acute liver failure (defined as the onset of jaundice, hepatic coagulopathy, and hepatic encephalopathy), which may eventually end in maternal death [ 68 , 69 , 70 ]. Pregnancy is likely to cause suppression of T cell-mediated immunity (including suppression of CD4 cells) and increased production of steroid hormones, leading to increased virus replication [ 71 , 72 ]. Upon entering the body, the virus can be present without visible antigens in a partially enveloped phase, which enables it to hide its existence from opsonizing antibodies.…”
Section: Hev Infections In Pregnant Womenmentioning
confidence: 99%
“…This in turn suppresses cellular immunity at the circulation interface, between embryonic tissue and the uterine lining (maternal–fetal interface) and allows the transmission of HEV. Moreover, there are reports of HEV replicating within the placenta [ 71 , 73 ]. Therefore, rapid, effective response to invasive pathogens is vital to avoid massive maternal infection and consequent fetal complications [ 67 ].…”
Section: Hev Infections In Pregnant Womenmentioning
confidence: 99%